Consulting Committee - Editor- , in -Chief (Basra studies journal, 2025)
The research should be in public law, or private law, and the study of judicial decisions related to each law, as well as the study of comparative laws, with the aim of developing laws in force.Concerned with legal studies of a practical and theoretical.